2019
DOI: 10.1016/j.jvolgeores.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

In situ terminal settling velocity measurements at Stromboli volcano: Input from physical characterization of ash

Abstract: 9Ash particle terminal settling velocity is an important parameter to measure in order to 10 constrain the internal dynamics and dispersion of volcanic ash plumes and clouds that emplace 11 ash fall deposits from which source eruption conditions are often inferred. Whereas the total 12 Particle Size Distribution (PSD) is the main parameter to constrain terminal velocities, many 13 studies have empirically highlighted the need to consider shape descriptors such as the 14 sphericity to refine ash settling veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…In addition, ground tarpaulins were placed next to the disdrometer to collect ash samples for each event recorded by the disdrometer. Freret-Lorgeril et al (2019) demonstrated the influence of ash particle shape on disdrometer terminal settling velocity and size measurements. Since the disdrometer is designed to measure the shape of spherical droplets for meteorological applications, the shape of settling ash particles were constrained and determined with a morpho-grainsizer Morphologi G3 ® by Freret-Lorgeril et al (2019).…”
Section: The Optical Disdrometermentioning
confidence: 98%
See 3 more Smart Citations
“…In addition, ground tarpaulins were placed next to the disdrometer to collect ash samples for each event recorded by the disdrometer. Freret-Lorgeril et al (2019) demonstrated the influence of ash particle shape on disdrometer terminal settling velocity and size measurements. Since the disdrometer is designed to measure the shape of spherical droplets for meteorological applications, the shape of settling ash particles were constrained and determined with a morpho-grainsizer Morphologi G3 ® by Freret-Lorgeril et al (2019).…”
Section: The Optical Disdrometermentioning
confidence: 98%
“…The goal of our measurement campaign is to characterize quantitatively the sedimentation behavior of volcanic plumes with three techniques: (i) a 3 mm wavelength Doppler radar (95 GHz), designed to track ash in volcanic plumes ( Figure 1C); (ii) an optical disdrometer Parsivel 2 ( Figure 1C); and (iii) analyses of ground deposit samples acquired during the campaign (Freret-Lorgeril et al, 2019). In this study, it is important to note that each method detects a local Particle Size Distribution (PSD).…”
Section: The Measurement Campaign At Strombolimentioning
confidence: 99%
See 2 more Smart Citations
“…The Sakurajima Volcanological Observatory (SVO), Disaster Prevention Research Institute (DPRI) of Kyoto University operates a Particle-Size-Velocity (parsivel) disdrometer network in order to monitor ashfall over the volcano. Parsivel disdrometers are laser-optical disdrometers used to measure the number, size and fall speed of hydrometeors and ash particles [15,22]. The OTT Parsivel 2 disdormeters used have operating limits of 0.2-25 mm for the particle size and 0.2-20 m s −1 for the velocity.…”
Section: Introductionmentioning
confidence: 99%